Synthesis of zeolitic imidazolate frameworks (ZIF)-8 membrane and its process optimization study in separation of CO2 from natural gas - Lai, L.S. (John Wiley and Sons Ltd, 2017)
BACKGROUND: In this work, well-intergrown zeolitic imidazolate frameworks-8 (ZIF-8) membrane was synthesized through a microwave-assisted secondary solvothermal growth method. A solvent evaporation seeding method was applied prior to membrane growth. Subsequently, process optimization for the separation of CO2 from natural gas through the ZIF-8 membrane was studied using response surface methodology. The process variables studied included CO2 feed composition (36–83), total pressure difference (100–700 kPa) and temperature (303–343 K). Three empirical models were generated using a central composite design in order to study the interaction between the process variables and the responses, including CO2 permeance, CH4 permeance and CO2/CH4 separation factor. The optimum condition was then determined for maximum CO2 permeance and CO2/CH4 separation factor and minimum CH4 permeance. RESULTS: Using this method, ZIF-8 seeds of nano-size were well distributed on the support due to high nucleation rate at the supersaturation condition. The presence of heavy hydrocarbons affected CH4 permeance, attributed to the molar mass and viscosity. An optimum CO2 permeance of 2.76 × 10−8 mol m−2 s−1 Pa−1 and CO2/CH4 separation factor of 3.72 was obtained at 312 K, 100 kPa and 36 CO2 feed composition. The experimental results were in agreement with the predicted values with an average error lower than ± 7. CONCLUSION: Selective ZIF-8 membrane was successfully synthesized using a feasible and reproducible solvent evaporation seeding method. The experimental data for the optimum condition were in good agreement with the predicted data, showing the accuracy of the empirical models. © 2016 Society of Chemical Industry. © 2016 Society of Chemical Industry